KONSEP MATEMATIKA PADA TRADISI PERNIKAHAN SUKU TIDUNG - Azriah Azriah; Jailani Jailani; Herison Herison; Eva Julianingsih (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
In today's modern era, preserving culture is very important. One effort that can be made is to integrate culture into learning mathematics. This research is conducted to identify the mathematical concepts of the Tidung wedding ritual in Nunukan Regency, North Kalimantan. The mathematical concepts found can be used as material to integrate culture in learning mathematics. The concept of the program is known as ethnomathematics. This research is ethnographic. Mathematical concepts in the Tidung wedding tradition will be identified in the tools and activities of the wedding ritual. The data were obtained through direct observation, interviews, and documentation analysis. Data analysis was carried out in four stages: data reduction, data presentation, concluding, and checking the validity of the data using triangulation methods. The results showed that there were mathematical concepts in the tools used in the wedding procession. Tools that can be used in learning mathematics include bagas silow, dian, busak dian, nasi rasul, nasi pengantin, sirih pinang, selapah, pelujan, raja besila, gandur, batu asa, padaw, and panggaw. The identified mathematical concepts are cylinders, circles, cuboids, geometric transformations, regular polygons, half spheres, integrals, quadrilaterals, arithmetic sequences and series, congruences, number patterns, and triangles. Then, there are counting activities in the ritual activities of bepupur/pupuran and bejiu pengantin (bridal bath).TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//